EcoHealth 2014: Communicating complexity - Mehta-Bhatt, Purvi (International Livestock Research Institute, 2014)
In this film, Purvi Mehta-Bhatt, formerly with ILRI in India, speaks about communicating complexity within EcoHealth at the EcoHealth 2014 conference in Montreal, Canada on 15 August 2014.